2015
DOI: 10.3846/20294913.2015.1070772
|View full text |Cite
|
Sign up to set email alerts
|

Data Pre-Processing for Neural Network-Based Forecasting: Does It Really Matter?

Abstract: Abstract.This study aims to analyze the effects of data pre-processing on the forecasting performance of neural network models. We use three different Artificial Neural Networks techniques to predict tourist demand: multi-layer perceptron, radial basis function and Elman neural networks. The structure of the networks is based on a multiple-output approach. We use official statistical data of inbound international tourism demand to Catalonia (Spain) and compare the forecasting accuracy of four processing method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…This result coincides with that of Claveria et al (2017) for Catalonia, who analysed the effects of data pre-processing on the forecasting performance of NN models and found that the predictive accuracy of the models improved with seasonal adjusted data. Medeiros et al (2008) developed an alternative approach to analyse the demand for international tourism in the Balearic Islands.…”
Section: Most Of the Research On Tourism At Regional Level In Spain Fsupporting
confidence: 86%
“…This result coincides with that of Claveria et al (2017) for Catalonia, who analysed the effects of data pre-processing on the forecasting performance of NN models and found that the predictive accuracy of the models improved with seasonal adjusted data. Medeiros et al (2008) developed an alternative approach to analyse the demand for international tourism in the Balearic Islands.…”
Section: Most Of the Research On Tourism At Regional Level In Spain Fsupporting
confidence: 86%
“…In fact, this study showed that NN struggle to model and forecast when presented with raw data which has strong seasonality and trends. More recent evidence by Claveria et al (2017) provides further support for deseasonalizing series when forecasting with NN. Accordingly, it is clear that in contrast to our personal beliefs, many researchers argue in favour of deseasonalisation or detrending as the more suitable approach for improving the accuracy of NN forecasts.…”
Section: Introductionmentioning
confidence: 79%
“…However, more recent experiments suggest that deseasonalization prior to feeding data to the NNs is essential since NNs are weak in modelling seasonality. Particularly, Claveria et al (2017) empirically show for a tourism demand forecasting problem that seasonally adjusted data can boost the performance of NNs especially in the case of long forecasting horizons. Zhang and Qi (2005) conclude that using both detrending and deseasonalization can improve the forecasting accuracy of NNs.…”
Section: Modelling Seasonalitymentioning
confidence: 98%